1, 25-Dihydroxyvitamin-D3 prevents the development of diabetic cardiomyopathy in type 1 diabetic rats by enhancing autophagy via inhibiting the β-catenin/TCF4/GSK-3β/mTOR pathway. Issue 168 (April 2017) - Wei, Huili; Qu, Hua; Wang, Hang; Ji, Baolan; Ding, Yao; Liu, Dan; Duan, Yang; Liang, Huimin; Peng, Chuan; Xiao, Xiaoqiu; Deng, Huacong
Abstract: Diabetic cardiomyopathy (DCM) can increase the risk of heart failure and death in diabetic patients. However, no effective approaches are available to prevent its progression and development. Studies have shown that vitamin D is greatly implicated in cardiac hypertrophy and fibrosis, and there is a high prevalence of vitamin D deficiency in diabetic patients. In this study, we investigated whether 1, 25-Dihydroxyvitamin-D3 (1, 25D3) can improve DCM through a vitamin D receptor (VDR)-dependent mechanism associated with autophagy and the β-catenin/T-cell factor/lymphoid enhancer factor (TCF4)/glycogen synthase kinase-3β (GSK-3β)/mammalian target of rapamycin (mTOR) pathway. In this study, streptozotocin (STZ)-induced type 1 diabetic rats were established and were treated with 1, 25D3 and/or chloroquine and/or VDR gene silencing for 8 weeks before being sacrificed. Compared with untreated diabetic rats, 1, 25D3 partly attenuated the myocardial hypertrophy and interstitial fibrosis, improved cardiac function and restored the impaired cardiac autophagy in diabetic rats, all of which were reversed by silencing the VDR gene in diabetic rats. In high-glucose cultured H9C2 cells, 1, 25D3 increased autophagy in a dose-dependent manner. Besides, the β-catenin/TCF4/GSK-3β and mTOR signaling were activated both in diabetic rats and in high-glucose cultured H9C2 cells. Treatment with 1, 25D3 inhibited the β-catenin/TCF4/GSK-3β and mTOR signaling in H9C2 cells, whereas co-treatment with lithium chloride (LiCl) reversed this situation and abolished the beneficial effect of 1, 25D3 on autophagy. These data suggest that 1, 25D3 may improve DCM in type 1 diabetic rats by modulating autophagy through the β-catenin/TCF4/GSK-3β and mTOR pathway. Vitamin D may exist as a new therapeutic target for the treatment of DCM.